1991
DOI: 10.1128/aem.57.1.19-28.1991
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Size of Indigenous Rhizobial Populations on Establishment and Symbiotic Performance of Introduced Rhizobia on Field-Grown Legumes

Abstract: Indigenous rhizobia in soil present a competition barrier to the establishment of inoculant strains, possibly leading to inoculation failure. In this study, we used the natural diversity of rhizobial species and numbers in our fields to define, in quantitative terms, the relationship between indigenous rhizobial populations and inoculation response. Eight standardized inoculation trials were conducted at five well-characterized field sites on the island of Maui, Hawaii. Soil rhizobial populations ranged from 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
149
0
13

Year Published

1992
1992
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 350 publications
(167 citation statements)
references
References 27 publications
5
149
0
13
Order By: Relevance
“…Likewise, studies on soybean and other agricultural legumes showed that an increasing number of rhizobia in the host rhizosphere can result in a linear increase in nodulation (Elegba & Rennie 1984;Patrick & Lowther 1995;Deaker, Roughley & Kennedy 2004). However, inoculation effects can be negatively influenced by indigenous rhizobial populations with high nodulation competitiveness (Singleton & Tavares 1986;Thies, Singleton & Bohlool 1991). Like for O. glaberrima (Table S1), phylogenetically diverse bacteria have been isolated from Acacia nodules.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, studies on soybean and other agricultural legumes showed that an increasing number of rhizobia in the host rhizosphere can result in a linear increase in nodulation (Elegba & Rennie 1984;Patrick & Lowther 1995;Deaker, Roughley & Kennedy 2004). However, inoculation effects can be negatively influenced by indigenous rhizobial populations with high nodulation competitiveness (Singleton & Tavares 1986;Thies, Singleton & Bohlool 1991). Like for O. glaberrima (Table S1), phylogenetically diverse bacteria have been isolated from Acacia nodules.…”
Section: Discussionmentioning
confidence: 99%
“…In the USA, where soybean is also an important crop, there are frequent reports of a lack of response to inoculation in soils with few cells of established bradyrhizobia [22,27]. Contrarily, in Brazil ¢eld responses to inoculation can be obtained even in soils with up to 10 5 cells of soybean bradyrhizobia g 31 of soil [9,10,12,13,17,28,32].…”
Section: Discussionmentioning
confidence: 99%
“…First, additional variation in N 2 fixation could result from physiological controls at smaller scales, such as soil O 2 availability (Layzell and Hunt 1990). Second, rhizobial strains differ in their effectiveness, and may have differed in vetch nodules across farms, because background soil populations often occupy nodules despite inoculation (Thies et al 1991). Consequently, applying one B value across sites, to account for isotopic fractionation, may not fully meet the assumptions of the natural abundance method.…”
Section: Changes In Labile Organic Matter Pools With a Legumegrass MImentioning
confidence: 99%